Code Switching Used by Deny Sumargo in His Youtube Video “Curhat Bang” with Onadio Leonardo - I Gede Astena Largama Largama; Ni Made Verayanti Utami; Ida Ayu Mela Tustiawati (ELITE Association Indonesia, 2022)
The title of this article is Code Switching Used by Deny Sumargo in His Youtube Video Curhat Bang with Onadio Leonardo. This article focuses on finding utterances that contain Code-switching action. The goals of this article are to analyze the types of Code-switching that uttered by Deny Sumargo and his Guest Onadio Leonardo in his YouTube video. To answer the problem of this article, the researcher analyzes based on the theory Hoffman (1991). Descriptive qualitative method is the method that applied in analyzing the data by explaining descriptively the utterances that contain code switching into each type based on Hoffman’s (1991) classification. The results of this study are presented in three types of Code-switching, the first is Intra-sentential code-switching, second is Inter-sentential code-switching, and last is tag-switching.